SAT: Free Software for the Semi-Automated Analysis of Rodent Brain Sections With 2,3,5-Triphenyltetrazolium Chloride Staining - Shi, Xiao-Fang; Ai, Heng; Lu, Wen; Cai, Fuhong (Frontiers in Neuroscience, 2019)
Ischemic stroke opposes increasing burden on individuals, families and societies around the world. However, effective therapy or drug for ischemic stroke is in lack of implement so far. Therefore, animal model mimicking ischemic stroke in human is of great value for preclinical experiments. Middle cerebral artery occlusion (MCAO) in mice or rats and subsequent 2,3,5-triphenyltetrazolium chloride (TTC) staining of brain slice are commonly used methods in studying experimental animal ischemic stroke. In the present study, we presented a software named SAT for semi-automated analysis of TTC staining of brain slices, which is a very small size, easy and free to use software in personal computer for quantification of infarct size of brain slice with TTC staining captured by cell phone or scan system. We performed MCAO experiments and TTC staining. Afterwards, we utilized the SAT software to analyze the infarct size of brain slices with TTC staining. We found that the data of infarct size from the SAT and the data of infarct size from Image J were comparable, suggesting the software can be an alternative choice other than Image J in the field of ischemic stroke.